Liechtenstein : Assessment of the Supervision and Regulation of the Financial Sector Volume II-Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2003)
This report on the offshore financial center program contains technical advice and recommendations given by the staff team of the International Monetary Fund in response to Liechtenstein's request for technical assistance. It provides detailed assessment of observance of the Basel Core Principles for effective banking supervision, implementation of the International Organization of Securities Commissions (IOSCO) Objectives And Principles Of Securities Regulation, and observance of the International Association of Insurance Supervisors (IAIS) core principles. It also provides the methodology for Assessing Compliance with Anti-Money Laundering and Combating the Financing of Terrorism Standards, endorsed by the Financial Action Task Force.